Protection in the Grey Zone: Assessing HDP-Nexus Coherence for Protection to IDPs in the West Bank - Diez Landin,Johan (2025)
In the West Bank, a context of protracted displacement and institutional fragmentation, internally displaced persons remain structurally excluded from both humanitarian and national protection systems. Amid fragmented aid architecture and legal ambiguity, the Humanitarian-Development-Peace Nexus has been promoted as a framework for institutional coherence. Yet, it remains mired in a contested space between mandates, principles, and institutional logics – an ambiguous and precariously navigated space defined in academic literature as the grey zone. Within this fractured landscape, where internally displaced persons fall in the margins of visibility, social protection mechanisms emerge not only as technical tools, but as politically charged instruments with the potential to mediate the temporal and institutional protection gaps of the grey zone. However, its promise is contested in the deeply fractured and politically charged context presented in the West Bank, marked by a nearly eighty years long occupation, legal non-recognition of internally displaced persons, and exclusionary governance regimes. This paper examines the potential of the Social Protection and Cash and Voucher Assistance mechanism in the West Bank as a bridging instrument within the grey zone. Grounded in theories of structural violence (Galtung, 1969), inclusive citizenship (Kabeer, 2002; Lister, 2007), and transformative social protection (Devereux & Sabates-Wheeler, 2004), the study employed a qualitative case study design to uncover the routinized marginalization of exclusionary protection practices targeting internally displaced persons, and critically assesses how the social protection mechanism under study addresses, or reproduces, the structural exclusions shaping access to protection. Findings show that innovations in programming, coordination, and technical interoperability have demonstrated notable potential in enhancing institutional coherence and contributing to the tightening of the grey zone gap. However, advancements have been undermined by the structural marginalization embedded within the foundational architecture of the protection system, resulting in the reproduction of exclusion and harm for internally displaced persons. By interpreting the implications of these dynamics for the recognition, inclusion, and rights-claims of internally displaced persons, the study has found that the protection mechanism, while partially contributing to bridging the gaps of the grey zone, largely reproduces the structural marginalization of internally displaced persons. Amid escalations of military and settler violence in the West Bank, largely obscured from international attention, the findings present an urgent need to improve the protection frameworks for systemically marginalized populations in the West Bank and address the empirical void surrounding institutional response to displacement under occupation.
Keywords: Social Protection; Humanitarian-Development-Peace Nexus; Internally Displaced Persons; Structural Violence; Inclusive Citizenship; Transformative Social Protection; Fragile and Conflict-Affected Settings; the West Bank; Palestine.